Design factor identification for developing a sustainable product-service systems - Teo, Brandon Hao Sheng (2017)
In order to develop a sustainable Product-Service System (PSS), this study utilised the existing product development model, service development model and product-service platform model to achieve the objective. The objective of this study is to implement and embody service design model into the existing PSS model to facilitate the designers in developing the product in the complex business ecosystem. This report proposes a new PSS to enhance the serviceability of the product design. Various methodologies were used to distinguish the gap between the product and service model. The proposed service design model was developed based on the interaction between the product functions and the service functions, focusing on the potential consumer’s behaviour. A Smart TV was used as a case study to validate the effectiveness of the new proposed PSS model.